Synthesis of [{AgO2CCH2OMe(PPh3)}n] and theoretical study of its use in focused electron beam induced deposition - Tamuliene, Jelena; Noll, Julian; Frenzel, Peter; Rüffer, Tobias; Jakob, Alexander; Walfort, Bernhard; Lang, Heinrich (Beilstein Journal of Nanotechnology, 2017)
The synthesis, chemical and physical properties of [AgO2CCH2OMen] (1) and [{AgO2CCH2OMe(PPh3)}n] (2) are reported. Consecutive reaction of AgNO3 with HO2CCH2OMe gave 1, which upon treatment with PPh3 produced 2. Coordination compound 2 forms a 1D coordination polymer in the solid state as evidenced by single crystal X-ray structure analysis. The coordination geometry at Ag+ is of the [3 + 1] type, whereby the carboxylate anions act as bridging ligands. The formation of PPh3–Ag(I) coordinative bonds results in distorted T-shaped AgPO2 units, which are stabilized further by an additional O–Ag dative bond. TG and TG–MS measurements show that 1 and 2 decompose at 190–250 °C (1) and 260–300 °C (2) via decarboxylation, involving Ag–P (2), C–C and C–O bond cleavages to give elemental silver as confirmed by PXRD studies. In order to verify if polymeric 2 is suitable as a FEBID precursor for silver deposition, its vapor pressure was determined (p170 °C = 5.318 mbar, ∆Hvap = 126.1 kJ mol−1), evincing little volatility. Also EI and ESI mass spectrometric studies were carried out. The dissociation of the silver(I) compound 2 under typical electron-driven FEBID conditions was studied by DFT (B3LYP) calculations on monomeric [AgO2CCH2OMe(PPh3)]. At an energy of the secondary electrons up to 0.8 eV elimination of PPh3 occurs, giving Ag+ and O2CCH2OMe−. Likewise, by release of PPh3 from [AgO2CCH2OMe(PPh3)] the fragment [AgO2CCH2OMe]− is formed from which Ag+ and O2CCH2OMe− is generated, further following the first fragmentation route. However, at 1.3 eV the initial step is decarboxylation giving [AgCH2OMe(PPh3)], followed by Ag–P and Ag–C bond cleavages.
Keywords: DFT; DSC; FEBID; silver(I) carboxylate; solid-state structure; TGA

(untitled) - Utke, I.; Jenke, M. G.; Roeling, C.; Thiesen, P. H.; Iakovlev, V.; Sirbu, A.; Mereuta, A.; Caliman, A.; Kapon, E. (Nanoscale, 2011)

(untitled) - Toth, M.; Lobo, C.; Friedli, V.; Szkudlarek, A.; Utke, I. (Beilstein J. Nanotechnol., 2015)

(untitled) - Höflich, K.; Becker, M.; Leuchs, G.; Christiansen, S. (Nanotechnology, 2012)

(untitled) - Huth, M.; Porrati, F.; Schwalb, C.; Winhold, M.; Sachser, R.; Dukic, M.; Adams, J.; Fantner, G. (Beilstein J. Nanotechnol., 2012)

(untitled) - Botman, A.; Mulders, J. J. L.; Hagen, C. W. (Nanotechnology, 2009)

(untitled) - Adner, D.; Noll, J.; Schulze, S.; Hietschold, M.; Lang, H. (Inorg. Chim. Acta, 2016)

(untitled) - Niskanen, A.; Hatanpää, T.; Arstila, K.; Leskelä, M.; Ritala, M. (Chem. Vap. Deposition, 2007)

Comprehensive Inorganic Chemistry II - Lang, H.; Dietrich, H. (S. 4.10 – Metals – Gas-Phase Deposition and Applications, 2013)

The Chemistry of Metal Enolates - Lang, H.; Buschbeck, R. (Deposition of metals and metal oxides by means of metal enolates, 2009)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)

Synthese und Reaktionsverhalten von Übergangsmetallkomplexen sowie deren Verwendung in der Homogenen Katalyse und Metallabscheidung - Jakob, A. (TU Chemnitz, 2009)
http://nbn-resolving.de/urn:nbn:de:bsz:ch1-200900713

(untitled) - Dobbs, K. D.; Hehre, W. J. (J. Comput. Chem., 1987)

Part B: Applications in Corrdination, Organometallic, and Bioinorganic Chemistry - Nakamoto, K. (John Wiley & Sons, Inc., 2009)

(untitled) - Fisher, J. S.; Kottke, P. A.; Kim, S.; Fedorov, A. G. (Nano Lett., 2015)

(untitled) - Römbke, P.; Schier, A.; Schmidbaur, A.; Cronje, S.; Raubenheimer, R. (Inorg. Chim. Acta, 2004)

(untitled) - Cingolani, A.; Effendy; Pettinari, C.; Skelton, B. W.; White, A. H. (Inorg. Chim. Acta, 2006)

(untitled) - Tuchscherer, A.; Georgi, C.; Roth, N.; Schaarschmidt, D.; Rüffer, T.; Waechtler, T.; Schulz, S. E.; Oswald, S.; Gessner, T.; Lang, H. (Eur. J. Inorg. Chem., 2012)

(untitled) - Dryden, N. H.; Vittal, J. J.; Puddephatt, R. J. (Chem. Mater., 1993)

(untitled) - Farrugia, L. J.; Evans, C. (J. Phys. Chem. A, 2005)